Phytroremediation technologies for treating industrial textile wastewater using eichhorina crassipes SP. pistia stratiotes SP. and typha latifolia SP. - Lee Weng Foo (School of Environmental Engineering, University Malaysia Perlis, 2014)
Based on this research, a study of phytoremediation techniques for the treatment of industrial textile wastewater by using three types of selected aquatic plants which known as Eichhornia Crassipes Species (ECs), Pistia Stratiotes Species (PSs), and Typha Latifolia Species (TLs) for overcome the current issue where textile wastewater still treated by using the conventional biological, chemical and physical treatment process with high costing and un-environmental. The textile wastewater contain high chemical oxygen demand (COD), biochemical oxygen demand (BOD), heat, color, acidity, basicity and other soluble substances (Ahn et al., 1999).